Application of Differential Transformation Method for Solving Eighth-order Boundary Value Problems - Hussin, Che Haziqah Che; Mandangan, Arif (Advanced Aspects of Engineering Research Vol. 15, 2021)
We used the Differential Transformation Method to solve linear and nonlinear eighth-order boundary value problems in this study. The error of DTM is then calculated, and the results are compared to those of other methods such as the modified implementation of the variational iteration method (MVAM), the homotopy perturbation method (HPM), and the modified Adomian decomposition method (MADM). We compared each method's errors to exact solutions. To demonstrate the precision and efficiency of the current method, we presented many numerical examples.In contrast to the results obtained by other methods, the DTM proved to be more reliable.